(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This thesis is devoted to the study of the mimetic expressions typical of the Uzbek people and their cultural, social and linguistic characteristics. Mimic expressions are an important part of national culture as a means of conveying a person’s inner feelings and mood through facial expressions. During the study, the types of mimetic expressions common among the Uzbek people, their meaning, use in social situations and their specific aspects in comparison with other cultures were analyzed. This thesis is of great importance for studying the non-verbal means of communication of the Uzbek people and including them in linguistic research